THE PROSPECT OF TOBACCO CONTROL REGIME IN UZBEKISTAN IN LIGHT OF POTENTIAL DISPUTE UNDER THE UK-UZBEKISTAN BIT - Tojiboyev, Sarvar Zafarovich (INTERNATIONAL CONFERENCES, 2022)
This thesis highlights the difficulties in improving tobacco control measures in the light of protection of public health and investment by transnational tobacco company (BAT). Above-mentioned evidences prove that developing states face great challenges in implementing effective tobacco control scheme where the investor is major tobacco industry. Thereby, effective control policies are much needed when attracting an investment into domestic economy. Yet, the ability of BAT to shape public policies assumes particular importance in terms of WHO FCTC. After becoming a signatory party of the Convention, Uzbekistan must fulfill the requirements of the Convention and work out tobacco control regime. On the other hand, this move may also heighten the opportunity of BAT to shape the legislation or to encourage the pre-emptive adoption of ineffective measures.